Efek Intensi Pengunduran Diri Tenaga Kependidikan dan Lingkungan Organisasi dengan Kinerja Sebagai Variabel Mediasi Terhadap Pengembangan Karir dalam Era Digital di Sekolah Swasta - Willy Chandra (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the effect of the intention to leave educational staff and the organizational environment with performance as a mediating variable on career development in the digital era in private schools. This study used a quantitative approach with PLS-SEM data analysis to test the hypothesis. The research instrument used a questionnaire of 87 respondents using simple random sampling. The results of this study indicated that performance mediated the relationship between the intention to resign from educational staff and positive career advancement. On the other hand, performance mediated the relationship between the organizational work environment and negative career advancement. The work environment and intention to resign were positively related, and the organizational work environment did not positively affect performance. Overall, the analysis of the study's findings is important in providing new insights and valuable implications for improving teacher careers, as well as a value of optimism for administrators of primary and secondary education institutions in presenting policies that will impact enhancing teaching staff careers.